Ideological Contestation on the Production of Gender Exegesis within Institutional Quranic Interpretation in Indonesia - Bambang Husni Nugroho; Ahmad Mustaniruddin; Ahmad Taufik (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2024)
The exegetical products concerning women in institutional Quranic interpretations in Indonesia are significantly influenced by ideological contestation, cultural and social structures, and the political authority behind the exegetical writing teams. Consequently, textual comprehension may become biased and not entirely objective. Given this, exploring the ideological aspects underlying the production of religious texts is of paramount importance. This study employs a descriptive-analytical method with Michael Foucault's power relations approach to uncover the ideological dimensions behind exegetical production. Through this approach, the research addresses how societal social structures and state ideologies can influence the production of exegeses regarding women's roles and status in institutional interpretations in Indonesia. The study found that the interpretation of women's leadership in the Thematic Quranic Exegesis of Indonesian Ministry of Religious Affairs of the Republic of Indonesia is not only influenced by factors such as gender, women's characteristics, perceived female inability to address state issues, and the entrenched patriarchal culture in Indonesia, but also by motives of ideological contestation underlying interpretative production. Contextually, this exegesis was produced by the Ministry of Religious Affairs in 2009 during a presidential election contest between male and female candidates. The research concludes that exegetical production in Indonesia is affected by social contexts and power ideologies. The primary contribution of this study lies in tracing the aspects of ideological contestation, societal social structures, and the role of those in power behind the emergence of gender-related exegetical products in Indonesia.